The quality of nursing service management in South African hospitals - Marie Muller (AOSIS, 2000)
The purpose of this study is to determine - explore and describe - the quality of nursing service management in South African hospitals. A combined qualitative and quantitative pre- and post-test research strategy, in accordance with the COHSASA programme, was utilised. The hospitals implement the national standards during the preparatory phase, after having entered into an agreement with COHSASA. They determine their baseline status by means of an assisted self-evaluation. This is followed by an external survey phase where the hospital's compliance with the standards is evaluated. The nursing service is one of the professional services included in the accreditation programme. Their performance is compared with selected other professional services and their compliance with the core elements is also evaluated. The nursing services in South Africa are compliant with the national standards. The deficiencies are mainly within the quality improvement programmes that require further development and refinement.